Students’ Level of Understanding of Fiqh Ubudiyah and Its Implications in Daily Life - Fuad Hasyim; Ari Susetiyo; Farichatul Kholidah; Ainun Naimah; Romi Hasyim (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Islamic religious education plays a strategic role in shaping students’ character and religious behavior, particularly through the learning of fiqh ubudiyah, which is directly related to daily worship practices. However, differences in students’ levels of understanding often lead to variations in the implementation of worship. This study aims to describe the level of students’ understanding of fiqh ubudiyah at MA Al-Mahrusiyah 1 and to analyze its implications for their daily lives. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The findings indicate that students’ understanding of fiqh ubudiyah is generally categorized as good to very good, as reflected in their discipline in performing obligatory prayers, habituation of supplications and remembrance (dhikr), and the development of religious attitudes such as discipline and responsibility. Nevertheless, some students still require deeper understanding of the meaning and wisdom of worship to enhance consistency, particularly in practicing voluntary acts of worship. This study concludes that a strong understanding of fiqh ubudiyah plays a significant role in shaping students’ religious character. The contribution of this research lies in strengthening empirical evidence on the relationship between fiqh ubudiyah understanding and the practical implementation of worship within a pesantren-based madrasah context.